2020
DOI: 10.1002/smll.201906921
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Ge Vacancies and Ge Precipitates through Cr Doping for Realizing the High‐Performance GeTe Thermoelectric Material

Abstract: GeTe alloy is a promising medium‐temperature thermoelectric material but with highly intrinsic hole carrier concentration by thermodynamics, making this system to be intrinsically off‐stoichiometric with Ge vacancies and Ge precipitations. Generally, an intentional increase of formation energy of Ge vacancy by element substitution will lead to an effective dissolution of Ge precipitates for reduction in hole concentration. Here, an opposite direction of decreasing the formation energy of Ge vacancies is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
118
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 69 publications
4
118
1
2
Order By: Relevance
“…[ 38–40 ] Due to the similarly beneficial band structure and strong phonon anharmonicity with PbTe arising from the same chemical bonding mechanism, [ 41,42 ] comparable high peak ZTs ≈2 have continuously been reported in the system of GeTe. [ 29,43–56 ] One important difference between these two compounds is that GeTe undergoes the structural phase transition from the low‐temperature rhombohedral to the high‐temperature cubic phase at a critical temperature around 700 K. [ 57,58 ] The rhombohedral structure refers to a unit cell with parameters ( a = b = c and α = β = γ < 90°), belonging to the hexagonal crystal family. It can be regarded as a slightly distorted rock‐salt lattice along the [111] direction with a interaxial angle less than 90°.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…[ 38–40 ] Due to the similarly beneficial band structure and strong phonon anharmonicity with PbTe arising from the same chemical bonding mechanism, [ 41,42 ] comparable high peak ZTs ≈2 have continuously been reported in the system of GeTe. [ 29,43–56 ] One important difference between these two compounds is that GeTe undergoes the structural phase transition from the low‐temperature rhombohedral to the high‐temperature cubic phase at a critical temperature around 700 K. [ 57,58 ] The rhombohedral structure refers to a unit cell with parameters ( a = b = c and α = β = γ < 90°), belonging to the hexagonal crystal family. It can be regarded as a slightly distorted rock‐salt lattice along the [111] direction with a interaxial angle less than 90°.…”
Section: Figurementioning
confidence: 99%
“…For instance, it is found that Cr doping significantly reduced the formation energy from 1.02 to −0.08 eV at the valence band maximum (VBM). [ 53 ] As is known, suppressing the Ge vacancies is essential to ensure high charge carrier mobility that will be beneficial to achieve a high power factor. [ 47,50,66,72 ]…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations